FORECASTING OF INDONESIA'S POST-COVID-19 EXPORT VALUE USING SARIMA - Uqwatul Alma Wizsa; Wikasanti Dwi Rahayu; Septria Susanti (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2022)
The Covid-19 pandemic that entered Indonesia in early 2020 has more or less had an impact on Indonesia's economic growth. One of the important factors that are indicators of the ups and downs of the economy, especially in Indonesia, is export activities. The Covid-19 pandemic has had quite an impact on the total value of Indonesia's exports, especially from 2020 to 2021. The fluctuation in the export value has made researchers interested in forecasting the total export value, especially after the Covid-19 pandemic. Forecasting of the total value of exports can certainly be used as a reference for the government to determine the direction of policies toward export activities to increase Indonesia's economic growth. Export values usually have seasonal patterns. One of the time series analyses that can be applied to data on total export values is the SARIMA model. Especially after Covid-19, no related studies have been found that use the SARIMA model in predicting the total value of exports in Indonesia. Using reference data on the total export value of Indonesia from January 2019 to March 2022, the best model was obtained and met the assumptions of residual normality and residual freedom, namely the ARIMA model (0,1,1)(0,0,1)12 without an intercept with an AICc value of 675.5562. Forecasting the total export value from April 2022 to March 2023 using this model indicates that the export value will increase slowly but decrease in September 2022 and January 2023.